Effectiveness of diabetes self-management education and support interventions on glycemic levels among people living with type 2 diabetes in the WHO African Region: a Systematic Review and meta-analysis - Yimer, Yimer Seid; Addissie, Adamu; Kidane, Eshetu Girma; Reja, Ahmed; Abdela, Abdurezak Ahmed; Ahmed, Ahmed Ali (Frontiers in Clinical Diabetes and Healthcare, 2025)
BackgroundFor successful glycemic control, diabetes control requires a comprehensive management plan in which patients are educated and supported to make informed decisions about diet, exercise, weight control, blood glucose monitoring, taking medication, and regular screening for complications. Current evidence on the effectiveness of diabetes self-management education and support (D-SMES) interventions on blood glucose control is mixed, with some studies pointing to significant glycemic control benefits, whereas others have shown no significant benefits.ObjectiveThis systematic review and meta-analysis (SRMA) was conducted to evaluate the effectiveness of D-SMES interventions compared with usual care in controlling blood glucose levels among people living with type 2 diabetes (T2DM) in the World Health Organization (WHO) Africa Region and to describe the core components of D-SMES interventions.MethodsWe performed a SRMA of D-SMES interventions for managing T2DM in the WHO Africa Region. We searched PubMed, CINAHL, the Cochrane Central Register of Controlled Trials (CCRCT), and Google Scholar from inception to May 5, 2025, for studies that were randomized control trials that reported glycated hemoglobin (HbA1c) or fasting blood sugar (FBS) as outcome measures and were delivered to adults with T2DM. The methodological quality of the included studies was assessed via the Cochrane risk of bias tool (RoB2). Random effects model meta-analysis was used to estimate the population average pooled standard mean difference (Hedges’ g) for HbA1c with 95% CIs.ResultsWe screened the title/abstract records of 350 studies, of which 19 studies with a total of 3759 participants (1866 in the D-SMES group and 1893 in the usual care group) were included in the meta-analysis of HbA1c. The meta-analysis revealed a significant overall effect of D-SMES interventions on HbA1c among people living with T2DM in the WHO African Region (SMD = -0.468 with a 95% CI of -0.658 to -0.279, I2 = 85.5%). nine of the nineteen included studies reported significant effects. We would expect that in some 95% of all populations comparable to those in the analysis, the true effect size would fall between -1.27 and 0.34 (prediction interval). Of the 19 included studies, 15 had a low risk of bias, two had high risk, and two raised some concerns based on the Cochrane RoB 2 tool.ConclusionsDiabetes self-management education and support interventions are moderately effective in controlling blood glucose levels in T2DM patients within the WHO African region.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO, identifier CRD42022375732.